Glistening phenomenon in acrylic hydrophobic intraocular lenses – how do perioperative factors and concomitant diseases effect it’s incidence and severity - Godlewska, Aleksandra; Owczarek, Grzegorz; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
The aim : To evaluate the effect of selected perioperative factors and concomitant diseases on glistening of acrylic hydrophobic intraocular lens after phacoemulsification in a prospective study. Material and methods : 252 consecutive patients undergoing phacoemulsification with IOLs AcrySof IQ implantation were enrolled. The relationship between glistening and such factors as time of the surgery, the mean power and time of ultrasound energy, temperature of infusion fluids, type of cartridge, mean power of intraocular lens, trypan blue staining as well as some concomitant systemic and local diseases were analysed. The aforementioned factors were assessed a month 1. and 6. as well as after 1 and 2 years postoperatively. Results : Glistening incidence and severity increased significantly at each follow up. The use of cartridge D during intraocular lens implantation was related with significantly higher incidence of glistening as compared to using cartridge C. Higher refractive power of intraocular lens was related with increased incidence of glistening. Significantly higher intensity of the glistening was assessed in patients who suffered from diabetes. In turn, patients with uveitis presented with statistically lower severity of glistening. There was no association between other analysed factors and glistening. Conclusion : Glistening commonly occurs in patients after phacoemulsification and acrylic hydrophobic intraocular lenses (AcrySof Alcon Labs) implantation. Some intraoperative factors such as refractive power of the lens and smaller diameter of the cartridge were assessed to be significantly correlated. It might indicate that potential damage to the intraocular lens may play a role in development of glistening. Significantly higher severity of glistening was shown in patients with diabetes, which may imply the role of breakdown of physiological intraocular barriers. It is further supported by the demonstrated lower intensity of glistening in patients uveitis receiving high intensity steroid therapy.